Monitoring Tegangan dan Arus Pada Panel Surya Menggunakan IoT - Sutikno, Tole; Alfahri, Jekson; Purnama, Hendril Satrian (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2023)
Solar panel is a potential technology for harvesting solar energy, especially in tropical countries like Indonesia. Currently, energy harvesting technology based on solar photovoltaic (PV) has reached an advanced stage and is widely applied to various applications. On the other hand, the massive number of PV-based solar power plants (PLTS) makes the maintenance process even more difficult. Therefore, we need a solution that can streamline this maintenance process. With the use Internet of Things (IoT) Technology, we can monitor the health conditions of PLTS online and real-time. This study uses the NodeMCU ESP8266 microcontroller and the INA219 sensor to monitor current and voltage at PLTS system, then the data will be sent via the internet to the Blynk application. The research method used is to collect data every 10 minutes in the morning, afternoon, and evening. The results showed that the use of the NodeMCU ESP8266 microcontroller and the Blynk IoT platform for solar panel current and voltage monitoring applications can reduce production costs with optimal and stable measurement and monitoring results. Keyword— Blynk; Internet of Things; Monitoring; NodeMCU; Solar Panel.